MR imaging in white matter diseases of the brain and spinal cord - Filippi, Massimo. (Medical radiology diagnostic imaging, 2005)
In recent decades, the use of neuroimaging techniques has resulted in outstanding progress in the diagnosis and management of neurological diseases, and this is particularly true of those diseases that affect the white matter of the brain and spinal cord. This book, written by internationally acclaimed experts, comprises a series of comprehensive and up-to-date reviews on the use of MR imaging in these major neurological conditions. The diverse available MR techniques, such as magnetization transfer MRI, diffusion-weighted MRI, MR spectroscopy, functional MRI, cell-specific MRI, perfusion MRI, and microscopic imaging with ultra-high field MRI, offer an extraordinarily powerful means of gaining fundamental in vivo insights into disease processes. The strengths and weaknesses of all these techniques in the study of multiple sclerosis and other relevant diseases are extensively considered. After an introductory section on neuroimaging technology, subsequent sections address disorders of myelination, demyelinating diseases, immune-mediated disorders, and white matter disorders related to aging and other conditions. This book provides a valuable summary of the state of the art in the field, and defines important areas for future research. MR techniques: principles -- Basis of MRI contrast -- Hardware for magnetic resonance imaging -- Spin- and gradient-echo imaging -- Fast imaging with an introduction to k-space -- Magnetization transfer -- Quantitative diffusion imaging -- MR methods to measure cerebral perfusion -- Functional MRI -- MR spectroscopy -- Molecular imaging and high-field MRI in multiple sclerosis -- Disorders of myelination -- MR imaging of brain development -- Imaging of inherited and acquired metabolic brain disorders -- Proton MR spectroscopy in metabolic disorders of the central nervous system -- Demyelinating diseases -- conventional MRI techniques in multiple sclerosis -- Multiple sclerosis: other MR techniques -- Variants of multiple sclerosis -- Acute disseminated encephalomyelitis -- Demyelinating diseases of the spinal cord -- Demyelinating diseases of the optic nerve -- Immune-mediated disorders -- Primary angiitis of the central nervous system -- Neuro-psychiatric systemic lupus erythematosus -- Non-MS inflammatory diseases of the CNS: MR features in addition to the white matter -- White matter pathology in systemic immune-mediated diseases -- White matter disorders related with aging -- Neuroimaging of normal brain aging -- White matter abnormalities in patients with cerebrovascular disease -- Neurodegenerative diseases with associated white matter pathology -- White matter changes secondary to other conditions -- Viral and non-viral infections in immuno-competent and immunocompromised patients -- Neoplastic disorders -- Head trauma -- Psychiatric disorders.